A systematic review of the mdma model to address social impairment in autism - Chaliha, D.; Mamo, John; Albrecht, Matthew; Lam, Virginie; Takechi, Ryu; Vaccarezza, Mauro (BENTHAM SCIENCE PUBL LTD, 2021)
Background: Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder characterised by repetitive behaviours, cognitive rigidity/inflexibility, and social-affective impairment. Unfortunately, no gold-standard treatments exist to alleviate the core socio-behavioural impairments of ASD. Meanwhile, the prosocial empathogen/entactogen 3,4-methylene-dioxy-methamphetamine (MDMA) is known to enhance sociability and empathy in both humans and animal models of psychological disorders. Objective: We review the evidence obtained from behavioural tests across the current literature, showing how MDMA can induce prosocial effects in animals and humans, where controlled experiments were able to be performed. Methods: Six electronic databases were consulted. The search strategy was tailored to each database. Only English-language papers were reviewed. Behaviours not screened in this review may have affected the core ASD behaviours studied. Molecular analogues of MDMA have not been investigated. Results: We find that the social impairments may potentially be alleviated by postnatal administration of MDMA producing prosocial behaviours in mostly the animal model. Conclusion: MDMA and/or MDMA-like molecules appear to be an effective pharmacological treatment for the social impairments of autism, at least in animal models. Notably, clinical trials based on MDMA use are now in progress. Nevertheless, larger and more extended clinical studies are warranted to prove the assumption that MDMA and MDMA-like molecules have a role in the management of the social impairments of autism.